Analisis Faktor-faktor yang Memengaruhi Produksi Susu Sapi Perah pada Kelompok Tani Ternak di Kecamatan Gunungpati Kota Semarang - Virginaura, Fionni Athaya; Ekowati, Titik; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Gunungpati District is a center for dairy milk production in Semarang City because it has the highest number of dairy cows. However, the dairy farming business in Gunungpati District face issues that the milk production is suboptimal, variable, and uncertain. The purpose of this study is to analyze and examine the dairy milk production and the factors that affecting it in farmer groups in Gunungpati District, Semarang City. The research was conducted in the farmer groups including Rejeki Lumintu and Rejo Makmur in Sumurrejo Village, Pangudi Mulyo in Nongkosawit Village, Lestari in Plalangan Village, Rukun Makmur in Cepoko Village, Mekarsari in Mangunsari Village, and Sido Makmur in Jatirejo Village from November to December 2023. The research method used was a census or total sampling method, where all members who owned lactating dairy cows from the seven farmer groups were used as samples. The data obtained were then processed and analyzed using descriptive analysis and multiple linear regression analysis methods. The results showed that the average production generated by one lactating dairy cow per day in the Gunungpati District was 9.88 liters. Simultaneously, or together, all independent variables significantly influenced the amount of milk production. Partially, the number of lactating cows, the amount of concentrated feed, the amount of tofu waste feed, and the age of the dairy cow, significantly influenced the amount of milk production. On the other hand, the amount of forage feed and the duration of farming did not significantly affect the amount of milk production.